2017
DOI: 10.1186/s12889-017-4669-x
|View full text |Cite
|
Sign up to set email alerts
|

Workplace sexual harassment and depressive symptoms: a cross-sectional multilevel analysis comparing harassment from clients or customers to harassment from other employees amongst 7603 Danish employees from 1041 organizations

Abstract: BackgroundPrevious research has reported that sexual harassment can lead to reduced mental health. Few studies have focused on sexual harassment conducted by clients or customers, which might occur in person-related occupations such as eldercare work, social work or customer service work. This study examined the cross-sectional association between sexual harassment by clients or customers and depressive symptoms. We also examined if this association was different compared to sexual harassment conducted by a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
74
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 75 publications
6
74
2
2
Order By: Relevance
“…This variation might be due to these areas require much interpersonal interaction that could make them vulnerable to violence. However, in a study done in Denmark and Danish workplaces, participants employed in care work were more often exposed to sexual violence by clients and customers than participants employed in private service, professional work, building and construction, and industrial work [16]. This variation might be due to a difference in the study area in which the study done in Denmark, and Danish workplaces were conducted in different areas.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This variation might be due to these areas require much interpersonal interaction that could make them vulnerable to violence. However, in a study done in Denmark and Danish workplaces, participants employed in care work were more often exposed to sexual violence by clients and customers than participants employed in private service, professional work, building and construction, and industrial work [16]. This variation might be due to a difference in the study area in which the study done in Denmark, and Danish workplaces were conducted in different areas.…”
Section: Discussionmentioning
confidence: 97%
“…Whereas, in a study conducted in Nigeria the perpetrators were clients and managers [13]. Similarly, in a study done in Denmark and Danish workplaces sexual violence was conducted by colleagues, supervisors, subordinates [16]. This difference is due to the time gap, study design, and a difference in sociodemographic status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual harassment continues to be a 'systemic trauma' (Fitzgerald, 2017) for women in the workplace, with consequences for victims that include depression (Friborg et al, 2017;Houle, Staff, Mortimer, Uggen, & Blackstone, 2011), burnout (Takeuchi et al, 2018), anxiety (Mushtaq, Sultana, & Imtiaz, 2015) and even post-traumatic stress disorder (Avina & O'Donohue, 2002;see Chan, Lam, Chow, & Cheung, 2008, or Sojo, Wood, & Genat, 2016, for meta-analyses and a review of health effects). All of this is in addition to the effects on women's careers: harassment may make them more likely to quit jobs, even when doing so is economically disadvantageous (McLaughlin, Uggen, & Blackstone, 2017), with long-term economic effects.…”
Section: Introductionmentioning
confidence: 99%
“…It is controversial whether there are gender differences in the association between sexual harassment and depression. Some studies have shown that there are gender differences in the impact of sexual harassment on depression, while others report that there are no gender differences . Furthermore, no previous research has reported the prevalence of sexual harassment, and examined the association between sexual harassment and depressive symptoms in South Korea.…”
Section: Introductionmentioning
confidence: 99%